Statistical Study on the Effect of Meridional Neutral Wind on the Occurrence of Post‐Sunset Equatorial Ionospheric Irregularities - Bantayehu Aderaw; Melessew Nigussie (Space Weather)
Abstract The navigation and radio communication systems experience significant disruptions due to post‐sunset equatorial ionospheric irregularities. There is ongoing debate regarding the impact of meridional/trans‐equatorial wind speed on these irregularities, though it is widely agreed that the Pre‐Reversal Enhancement (PRE) plasma vertical drift velocity plays a key role in their occurrence. In this study, it is examined how F‐layer meridional neutral winds affect the post‐sunset equatorial ionospheric irregularities using GOCE satellite data in the years 2012–2013 employing statistical analysis. The Rate of Total Electron content (TEC) Index (ROTI) is commonly used to monitor ionospheric irregularities. The finding reveals a strong correlation between ROTI values and the differences in meridional wind speeds at the north and south equatorial ionization anomaly (EIA) crests. Observations show that smaller speed differences (less than ∼5 m/s) between the north and south EIA crests support the formation of post‐sunset ionospheric irregularities, while larger speed differences (more than 5 m/s) do not support irregularity formation.